2019
DOI: 10.3892/ol.2019.10782
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA small nucleolar RNA host gene 7 is upregulated and promotes cell proliferation in thyroid cancer

Abstract: Thyroid cancer (THCA) is one of the most common types of endocrine cancer worldwide. However, the mechanisms underlying THCA progression have not been fully elucidated. Recent studies have demonstrated that long non-coding RNAs (lncRNAs) are dysregulated in human diseases, and are involved in regulating various biological processes. Furthermore, several reports have indicated that lncRNAs serve important roles in THCA. In the present study, a dataset from The Cancer Genome Atlas was used to analyze the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
4
1
Order By: Relevance
“…In addition, down-regulated MEG3 could affect OA progression through miR-16/SMAD7 axis [31]. lncRNA SNHG7 was reported to as an oncogene in several cancers [17,18,20]. However, contrary to the previous study [21], we found that SNHG7 expression was reduced in OA tissues compared with normal tissues and the level of IL-1β was increased in OA serum compared with normal serum.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In addition, down-regulated MEG3 could affect OA progression through miR-16/SMAD7 axis [31]. lncRNA SNHG7 was reported to as an oncogene in several cancers [17,18,20]. However, contrary to the previous study [21], we found that SNHG7 expression was reduced in OA tissues compared with normal tissues and the level of IL-1β was increased in OA serum compared with normal serum.…”
Section: Discussioncontrasting
confidence: 58%
“…Notably, studies have reported that lncR-NAs may acts as competitive RNA which competitively binds to target miRNAs to indirectly regulate mRNAs [15,16]. lncRNA SNHG7 (small nucleolar RNA host gene 7) has been demonstrated to participate in cell development and progression of many diseases, especially in cancers [17][18][19]. Previous studies showed that SNHG7 was upregulated in several cancers, such as glioblastoma, colorectal cancer, gastric cancer and esophageal cancer [19,20].…”
mentioning
confidence: 99%
“…The high expression levels of SNHG7 are correlated with advanced stages (III and IV) and shorter survival times in of thyroid cancer patients. Their funding showed that SNHG7 knockdown inhibits the cell proliferation and cell cycle progression of ATC cell line in vitro [ 24 ]. The molecular mechanism of ATC caused by upregulation of SNHG7 still remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…19 SNHG7 is also markedly upregulated in thyroid cancer samples, with high SNHG7 expression associated with shorter survival times. 20 Indeed, SNHG7 knockdown leads to a suppression of thyroid cancer cell proliferation and migration, and induction of apoptosis via downregulating the acyl-CoA synthetase long chain family member 1 (ACSL1) and the brain-derived neurotrophic factor (BDNF). 21,22 In addition, bioinformatics analysis showed SNHG7 was associated with the processes of "protein translation", "viral life cycle", "RNA processing", "mRNA splicing", "histone ubiquitination", "endoplasmic reticulum-to-Golgi vesicle-mediated transport", "sister chromatid cohesion", "DNA damage checkpoint regulation", "translation", and "the spliceosome", suggesting further research directions for this lncRNA.…”
Section: Thyroid Cancermentioning
confidence: 99%
“…21,22 In addition, bioinformatics analysis showed SNHG7 was associated with the processes of "protein translation", "viral life cycle", "RNA processing", "mRNA splicing", "histone ubiquitination", "endoplasmic reticulum-to-Golgi vesicle-mediated transport", "sister chromatid cohesion", "DNA damage checkpoint regulation", "translation", and "the spliceosome", suggesting further research directions for this lncRNA. 20 SNHG12 is also upregulated (by 3.8-fold) in papillary thyroid carcinoma (PTC) tissues compared to normal adjacent tissue samples. 23 High SNHG12 was associated with poorer progression in PTC in terms of tumor node metastasis (TNM) staging and lymph node metastasis (LNM).…”
Section: Thyroid Cancermentioning
confidence: 99%